(untitled) (Research, Society and Development, 2025)
The objective of this article is to analyze the influence of pricing on inventory control in a seafood restaurant in the state of Piauí, investigating the interrelationship between inventory management, strategic cost management, and pricing. Through a single case study and data collection using direct observation and document analysis techniques, it was possible to obtain the desired results. Preliminary results indicate that the absence of structured pricing criteria compromises the efficiency of inventory management, causing waste and making it difficult to adapt the business to market fluctuations. With the implementation of good pricing and inventory management practices, the restaurant obtained an increase in average monthly financial gain over the six months applied. In addition, acquiring more rigorous control of inputs and adjusting pricing to costs and demand allowed for a more sustainable and competitive operation. By exploring these aspects, the study offers support to improve business management in the sector, contributing to the economic sustainability of seafood restaurants in the region.